The Leadership Values Bureaucracy in the Battle of Uhud: the Analysis of Verse Ali Imran (3): 121 and 144 in Fazlur Rahman's Perspective - Majid, Abdul; Basri, Ahmad Faizal (Program Studi Ilmu Al-Qur`an dan Tafsir, Fakultas Ushuluddin, UIN Sunan Kudus, 2023)
After losing the Battle of Badr, the Quraysh polytheists returned to Medina with a mission of revenge. Abu Sufyan bin Harb's troops won over the Muslims of Medina in the battle of Uhud. Among the triggers for the defeat of the Muslim community in the Uhud War were the indiscipline and disobedience of some Muslim troops to the Prophet Muhammad. This study tries to interpret QS. Ali Imran (3): 121 and 144 through Fazlur Rahman's double movement approach. The moral values drawn from the story of the Uhud war in verse are leadership with the character of a good listener, tactical-critical and patient while being supported by followers' loyalty. Lastly, resignation can be used as a reference in carrying out the wheels of a good, compact government bureaucracy. A common goal and no party is harmed because of selfish personal interests. This character was practised by the Prophet Muhammad. in managing the people of Medina. Unfortunately, during the Uhud War, some Muslim troops were disobedient or loyal to the instructions of the Prophet Muhammad. This is the urgency of a relationship between leaders and the people they lead. Leaders with the character of good listeners, critical-tactical and patient but not followed by the loyalty of their people will not be able to produce a good government order to achieve common goals. Birokrasi Nilai Kepemimpinan dalam Perang Uhud: Analisis Ayat Ali Imran (3): 121 dan 144 dalam Perspektif Fazlur Rahman.Kaum musyrik Quraish setelah kalah pada perang Badar, mereka kembali ke Madinah dengan misi balas demdam. Pasukan Abu Sufyan bin Harb berhasil menang atas kaum Muslimin Madinah di perang Uhud. Di antara pemicu kekalahan umat Islam dalam perang Uhud adalah ketidakdisiplinan dan ketidaktaatan sebagian pasukan Muslim pada Nabi Muhamamd Saw. Penelitian ini mencoba manafsirkan QS. Ali Imran (3): 121 dan 144 melalui pendekatan double movement Fazlur Rahman. Adapun nilai moral yang bisa diambil dari kisah perang Uhud dalam ayat tersebut adalah kepemimpinan dengan karakter pendengar yang baik, taktis-kritis dan sabar seraya didukung oleh loyalitas pengikut, dan yang terakhir tawakkal bisa dijadikan acuan dalam menjalani roda birokrasi pemerintah yang baik, kompak, tercapainya suatu tujuan bersama, serta tidak ada pihak yang dirugikan karena hanya sebab kepentingan pribadi yang egois. Karakter tersebut telah dipraktikan oleh Nabi Muhamamd Saw. dalam mengelola masyarakat Madinah. Sayangnya pada perang Uhud ada sebagian pasukan Muslim yang tidak taat atau loyal dengan instruksi Nabi Muhammad. Inilah urgensi ada keterkaitan antara pemimpin dan masyarakat yang dipimpinnya. Pemimpin berkarakter pendengar yang baik, kritis-taktis dan sabar namun tidak diikuti dengan loyalitas masyarakatnya tidak akan mampu menghasilkan tatanan pemerintah baik untuk mencapai tujuan bersama.